THE PRACTICE OF USING REMOTE PATIENT CARE WITHIN THE TELEMEDICINE SERVICE - A.B. ZUDIN (Avicenna Tajik State Medical University, 2020)
Objective: To consider the development of telemedicine as an auxiliary tool for additional diagnostics, treatment correction and disease prevention. Methods: The research is based on an EY survey of medical organizations conducted for 2018 and 2019 in the framework of a study on the commercial medicine market and the healthcare system in Russia on topical issues and problems of the healthcare sector development. The study was conducted from August to December 2019; top managers of 25 largest private medical organizations, whose geography of activity covers 30 entities of the Russian Federation, took part in the survey. Results: The study showed that some of the interviews (43%) observed resistance to the development of the health service by doctors and medical personnel who remained a supporter of classical methods of providing medical care at a proper time and nor ready to provide remote counselling to patients. As a reason for the inert participation by medical professionals in telemedicine projects, 33% of respondents indicated low demand by patients and the peculiarities of the Russian's mentality, 19% noted a misunderstanding of telemedicine. Some respondents (12%) see the telemedicine projects as the State social function for low-income citizens who live in remote areas and where there is no qualified medical staff. Conclusion: Most of the study participants expressed confidence that telemedicine services in the future will enter everyday life as a patient-friendly element of medical services, but it won't become a direction that brings great profit to the private medical sector.